2013
DOI: 10.1002/chir.22237
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Natural Occurrence of L‐ Versus D‐Pipecolic Acid: A Review

Abstract: Pipecolic acid naturally occurs in microorganisms, plants, and animals, where it plays many roles, including the interactions between these organisms, and is a key constituent of many natural and synthetic bioactive molecules. This article provides a review of current knowledge on the natural occurrence of pipecolic acid and the known and potential significance of its L- and D-enantiomers in different scientific disciplines. Knowledge gaps with perspectives for future research identified within this article in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 119 publications
(317 reference statements)
0
35
0
Order By: Relevance
“…Because d ‐pipecolate decreased cell viability, the mechanism appears to be independent of pipecolate oxidase activity, which is specific for l ‐pipecolate [Matsumoto et al, ]. Different roles for d ‐ and l ‐pipecolate have also been found in other biological contexts such as l ‐pipecolate acting as an anti‐hypertensive by competitively inhibiting the angiotensin I‐converting enzyme, whereas, the d ‐enantiomer does not have an antihypertensive function [Vranova et al, ]. Future studies will investigate the protective role of pipecolate metabolism and downstream pathways involving mTORC2, Akt and FoxO3 using other cell types to broaden our understanding of how pipecolate impacts the cellular redox environment.…”
Section: Discussionmentioning
confidence: 99%
“…Because d ‐pipecolate decreased cell viability, the mechanism appears to be independent of pipecolate oxidase activity, which is specific for l ‐pipecolate [Matsumoto et al, ]. Different roles for d ‐ and l ‐pipecolate have also been found in other biological contexts such as l ‐pipecolate acting as an anti‐hypertensive by competitively inhibiting the angiotensin I‐converting enzyme, whereas, the d ‐enantiomer does not have an antihypertensive function [Vranova et al, ]. Future studies will investigate the protective role of pipecolate metabolism and downstream pathways involving mTORC2, Akt and FoxO3 using other cell types to broaden our understanding of how pipecolate impacts the cellular redox environment.…”
Section: Discussionmentioning
confidence: 99%
“…Pipecolic acid (PA) is a diagnostic marker of pyridoxinedependent epilepsy (Plecko et al, 2005), which is synthesized in brain and accumulated in physiological fluids of humans with peroxisomal disorders (Vranova et al, 2013). The activities of some antioxidant enzymes, such as catalase and glutathione peroxidase, were significantly decreased by PA (Dalazen et al, 2014).…”
Section: Potential Neurotoxicity Of Asmentioning
confidence: 99%
“…Here we showed that F. oxysporum c8D produced trans-4-L-HyPip in the culture medium using the substrate of Pip4Hs, L-Pip. Now then, L-Pip is produced by microorganisms, plants, and animals and is therefore readily available for use by fungi (29). Alternatively, L-Pip might be synthesized by these fungi themselves.…”
Section: Figmentioning
confidence: 99%